Recent progress on nanomaterial-based electrochemical sensors for glucose detection in human body fluids - Singh K.; Maurya K.K.; Malviya M. (My University, 2025)
In the modern age, half of the population is facing various chronic illnesses due to glucose maintenance in the body, major causes of fatality and inefficiency. The early identification of glucose plays a crucial role in medical treatment and the food industry, particularly in diabetes diagnosis. In the past few years, non-enzymatic electrochemical glucose sensors have received a lot of interest for their ability to identify glucose levels accurately. Electrochemical biosensors are developing as a propitious solution for personalized health monitoring due to their accuracy, specificity, and affordability. This review article provides an observation of a variety of non-enzymatic glucose sensor resources, such as carbon nanomaterials, noble metals gold and silver, transition metal and their oxides, and porous material composites. Moreover, basic knowledge of the reaction mechanism of enzymatic and nonenzymatic glucose sensors are outlined and recent advancements in glucose sensors applications to various human body biofluids such as sweat, tears, urine, saliva, and blood are presented. Finally, this review summarizes electrochemical sensors for glucose detection in human body fluids, the challenges they faced, and their solutions. © The Author(s), under exclusive licence to Springer-Verlag GmbH Austria, part of Springer Nature 2025.